A study of crowd-collaborative learning: an empirical study. Issue 4 (19th November 2018) - Lin, Wen-Shan; Wang, Yi-Ju; Chen, Hong-Ren
Abstract : Purpose: Information technology is widely applied for completing group tasks and enhancing learning in computer-supported collaborative learning (CSCL) environment. Group members not only complete tasks but also learn ideas from other members of the group. These ideas can be better than what individual could come up with. As these ideas are referred as an upward comparison in the perspective of social comparison theory. However, there are limited studies that provide evidence in investigating how social comparison orientation (SCO) perceived by individual learner impacts on learning and group performance. The paper aims to discuss these issues. Design/methodology/approach: This study experimentally tackles this problem at both individual and group level. An experimental study was applied in this study. Structural equation modeling and hierarchical linear modeling approaches are used to validate the data. Findings: Results of 168 subjects reveal that SCO does have associations with group performance and learning performance respectively. Discussions and implications for literature and practice are given at the end of the paper. Originality/value: This study confirms that the social genesis occurs more effectively through social interactions in CSCL. It also extends our understandings about the impacts of SCO. Results reveal that the higher level of SCO adopted by group members, the higher level of social interactions at group level can be triggered. As a result, the group performance can be enhanced. On one hand, these findings bridge the research gap in terms of investigating the notion of SCT on CSCL. On the other hand, it provides a possible solution in alleviating the problem of social loafing as commonly observed in CSCL. Therefore, these findings fulfilled the two research objectives.